Loss of KCNJ15 expression promotes malignant phenotypes and correlates with poor prognosis in renal carcinoma - Liu Y; Wang H; Ni B; Zhang J; Li S; Huang Y; Cai Y; Mei H; Li Z (Cancer Management and Research, 2019)
Yang Liu,1,2,* Han Wang,1–3,* Beibei Ni,1,2 Jinghua Zhang,1,2 Shi Li,1,2 Yuqian Huang,1,2 Yanling Cai,1,2 Hongbing Mei,1–3 Zesong Li1,2 1Guangdong Key Laboratory of Systems Biology and Synthetic Biology for Urogenital Tumors, Shenzhen Second People’s Hospital, First Affiliated Hospital of Shenzhen University, Shenzhen 518035, China; 2Shenzhen Key Laboratory of Genitourinary Tumor, Shenzhen Second People’s Hospital, First Affiliated Hospital of Shenzhen University, Shenzhen, China; 3Department of Urinary Surgery, Shenzhen Second People’s Hospital, The First Affiliated Hospital of Shenzhen University, Shenzhen, China *These authors contributed equally to this work Background: KCNJ15 belongs to the inwardly rectifying potassium channel (KIR) family. Although members of the KIR family have been proven to play important roles in a variety of developmental processes, the molecular role and clinical effects of KCNJ15 in cancers remain unclear. Purpose: The aim of this study was to identify the expression, biological functions and molecular mechanisms of KCNJ15 in renal cell carcinoma (RCC).Methods: KCNJ15 mRNA expression was evaluated in kidney cancer tissue, paired adjacent normal tissue, and cell lines with qRT-PCR. KCNJ15 protein expression was investigated via western blotting and immunohistochemistry. In addition, the clinical and prognostic significance of KCNJ15 in RCC were assessed using Kaplan-Meier analysis and Cox proportional hazards analysis. In vitro, the effects of KCNJ15 on kidney cancer cells were evaluated by means of a cell counting kit-8, transwell assay along with flow cytometry, respectively. Moreover, the potential mechanism of KCNJ15 was demonstrated by Western blot. Results: Here, we first found that KCNJ15 was significantly downregulated in RCC, and this low expression was an independent prognostic factor for clear cell RCC (ccRCC). Moreover, KCNJ15 was associated with advanced TNM stage (n=150, p=0.014) and histological grade (n=150, p=0.045). Furthermore, KCNJ15 overexpression significantly inhibited RCC cell proliferation, migration, and colony formation, arrested the cell cycle and induced apoptosis of RCC cells in vitro. The inhibitory effect of KCNJ15 overexpression may be regulated by its effects on the epithelial mesenchymal transition (EMT) process and matrix metalloproteinase (MMP)-7 and p21 expression. Conclusion: These findings indicate that KCNJ15 may be a tumour suppressor in RCC and a possible target for RCC therapy. Keywords: KCNJ15, renal cell carcinoma, biomarker, tumor suppressor, prognosis